The implementation game the TRIPS agreement and the global politics of intellectual property reform in developing countries - Deere-Birkbeck, Carolyn, 1973- (Oxford : Oxford University Press, 2009)
This is a study of the politics surrounding the implementation of the WTO's Agreement on Trade Related Intellectual Property Rights (TRIPS), a controversial agreement administered by the World Trade Organization.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Agreement on Trade-Related Aspects of Intellectual Property Rights; Intellectual property (International law); Foreign trade regulation